Os desdobramentos e conflitos da criação do Parque Estadual Ilha do Cardoso sob a ótica do modelo GTP (Geossistema – Território- Paisagem) - Silva, Jéssica de Lima [UNESP] (2014)
One of the aspects of the discussion about territorial and environmental planning in Brazil is the question of protected areas, considered natural areas protected by the government whose principle is the biodiversity conservation. Its implementation in Brazil was after similar initiatives in other countries, and these experiences have been an influence to the installation of the national UCs. Due to the complexity of conflicts in protected areas it was decided to research a specific protected area, Parque Estadual Ilha do Cardoso (PEIC), with approaches related to the unfolding and conflicts emerged on its implementation. The research also emphasizes the different actors present in PEIC, their interests and perspectives related to the context in which it is found. Housed in the south-southeastern Brazil - marked by the proliferation of urban-industrial areas and rarity of preservation of natural ecosystems - PEIC consists of an area of high environmental preservation and the presence of traditional populations. The study adopted as the theoretical framework the GTP system (Geossystem - Territory - Landscape) wich was developed by geographer Georges Bertrand, proposes a systemic and integrated analysis of social-environmental dynamics. From this reference, the guide was based on methodological procedures: fieldwork in PEIC; technical visits to the base of the Park Management Council and the headquarters of the State of São Paulo Forest Foundation; conducting semi-structured interviews and analysis of PEIC policies planning...